A Review of Studies on Outcomes of Psychosocial Support Interventions: Nurturing Resilience in Looked-After Children - Amos Magut (Asian Social Work Journal, 2021)
Resilience is the quality of life in which a person is able to thrive against adverse internal and external conditions of life. This paper provides a framework for measuring resilience competency as a product of psychosocial support interventions. Resilience competency is one of the aims of psychological and social support given to persons who have undergone traumatic events or experiences. The researcher was biased towards the outcomes of psychosocial support given to looked-after children in care institutions. The paper is based on a review of literature on psychosocial support and resilience competency. The review focused on studies that have been published since the 1990s to date. The keywords used in the search for literature included psychosocial support, psychological support, social support, resiliency, resilience among children, looked-after children, psychosocial support and resilience. Based on the review of literature, the study found that researchers have identified many indicators of resiliency among looked-after children. Among these signs are: having a sense of purpose in life, exhibiting optimism, emotional hardiness or emotional intelligence and active coping with life’s challenges